Meningkatkan Hasil Belajar Matematika Materi Operasi Hitung Penjumlahan Dengan Metode Demonstrasi Dan Media Stik Es Krim - Putri Rahma Wulandary; Dina Syaflita (Algebra: Journal of Matematics, Statistics and Computation, 2024)
This research began with the low mathematics learning outcomes of students and their lack of engagement in learning. The study aimed to enhance mathematics learning outcomes related to addition operations using the demonstration method and ice cream stick media among Grade I students at SDN Kalisari 05. This type of research was a classroom action research consisting of four stages: planning, implementation, observation, and reflection. The subjects were 32 Grade I students from SDN Kalisari 05. The research was conducted over two cycles. The data showed an improvement in students' mathematics learning outcomes in solving addition operations in each research cycle. Initially, students' learning outcomes reached 28% of the Minimum Mastery Criteria (KKM) in the pre-cycle, then increased to 53% in Cycle I, and continued to improve to 87% in Cycle II. It was concluded that the application of the demonstration method and the use of ice cream stick media were effective in enhancing mathematics learning outcomes regarding addition operations in Grade I at SDN Kalisari 05.